State theories: a critical analysis - Das,Raju J. (1996)
This paper critically examines theories of the capitalist state. The state is a complex social relation with many aspects, each of which offers an entree into the study of the state as a whole; these aspects are like windows through which one may look at the state. The various approaches can be seen as conceptual dualisms consisting of opposing one-sided aspects. This method of analysis shows how one approach develops as a critique of another. It also shows that the state is a dialectical unity. The following dualistic approaches are analyzed: instrumentalism vs. structuralism; capital determination of the state vs. class struggle determination; and state-centered vs. society-centered approaches. In spite of the existence of so many approaches to the state, there are also several tendencies toward conceptual convergence, especially between instrumentalism and structuralism, class struggle and structuralism, and state-centered and society-centered approaches
Keywords: State, The